PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS VII DENGAN MENERAPKAN PEMBELAJARAN INKUIRI TERBIMBING - Galang Sasmito Aji; Mohammad Budiyanto (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the implementation of learning process while improving learning outcomes and students’ responses using a guided inquiry-based learning model on heat and transfer. This research method uses pre-experimental research with a research design of one group pretest and posttest with a research target of 22 students of class VII SMP Semen Gresik. The techniques of collecting data were observation, tests, and questionnaire and then was analyzed quantitatively and descriptively. The results that were obtained showed that the mode value of the results of the implementation of learning activities at the first and second meetings was included in the criteria for implementing very good learning, while the results of the students’ responses showed a positive response with the acquisition of very good criteria. The result of N-Gain test analysis acquire in the medium category so that students learning outcomes experienced a significant increase. Based on the description above, it can be concluded that there is an effect of guided inquiry-based learning in improving the learning outcomes of Class VII Junior High School students in the matter of heat and its transfer.